Biological Evaluation of Liposome‐Encapsulated Hemoglobin Surface‐Modified With a Novel PEGylated Nonphospholipid Amphiphile. Issue 8 (22nd April 2014) - Yadav, Vivek R.; Nag, Okhil; Awasthi, Vibhudutta
Abstract Traumatic injury is often associated with hemorrhagic shock. Liposome‐encapsulated hemoglobin (LEH) is being developed as an artificial oxygen carrier to address post‐hemorrhage oxygen and volume deficit. Here, we report a new composition of LEH based on the use of polyethylene glycol (PEG2K) conjugated with nonphospholipid hexadecylcarbamoylmethylhexadecanoate (HDAS) to modify the surface of LEH particles. LEH was manufactured by the high‐pressure homogenization method using dipalmitoylphosphatidylcholine (∼38 mol%), cholesterol (∼38 mol%), HDAS (∼20 mol%), and highly purified stroma‐free human hemoglobin. HDAS‐PEG2K was postinserted into the resultant LEH to generate HDAS‐PEG2K‐LEH. We investigated the potential immune response to HDAS‐PEG2K‐LEH in a mice model. At the same time, the preparation was tested in a rat model to study the effect of repeated HDAS‐PEG2K‐LEH injection over 4 weeks. We found that HDAS‐PEG2K modification substantially reduced the circulating levels of anaphylatoxins C3a and C5a, as well as plasma levels of thromboxane B2, in mice. Repeated injections of HDAS‐PEG2K‐LEH in rats did not appear to alter its clearance profile after 4 weeks of treatment. No antibody response against human hemoglobin or PEG was detected in rat plasma. Histological observations of lung, liver, spleen, and kidney were not significantly different between saline‐treated rats and HDAS‐PEG2K‐LEH‐treated rats. Immunohistochemical staining for rat heme oxygenase‐1 (HO‐1) did not show induced expression of HO‐1 in these organs. These results suggest that the new surface modification of LEH is immune‐neutral and does not adversely affect histology even after repeated administration.